PERAN SERVANT LEADERSHIP DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING - Dyta Dahliyanti; Zulfina Adriani (Jurnal Manajemen Terapan dan Keuangan, 2023)
As one of the institutions in public administration services, the Jambi City Regional Secretariat is expected to have an apparatus that has good work ability in serving regional apparatus and the community. Therefore, this study aims to determine the role of servant leadership and work motivation on employee performance through organizational commitment as an intervening variable at the Jambi City Regional Secretariat Office. This study uses a survey method by collecting primary data based on communication between researchers and respondents. The population in this study were all Civil Servants (PNS) at the Jambi City Regional Secretariat Office. The number of samples in this study were 97 people. The data analysis used for this research is quantitative data analysis regarding the direct influence of the independent variable on the dependent variable through the intervening variable (intervening variable). To do this test, use software in the form of Partial Least Square (PLS) version 3.0. As for the results of this study, servant leadership has a positive and significant influence on organizational commitment. Work motivation has a positive and significant influence on organizational commitment. Servant leadership has a positive and significant influence on employee performance. Work motivation has a positive and significant influence on employee performance. Organizational commitment has a positive and significant influence on employee performance. Servant Leadership has a positive and significant effect on employee performance mediated by organizational commitment. These results indicate that the better the Servant Leadership, the better the employee will be able to create a strong commitment so that in the end it will have an effect on improving performance. Work motivation has a positive and significant influence on employee performance mediated by organizational commitment. Servant Leadership and Work Motivation have a positive and significant influence on employee performance mediated by organizational commitment. This is evidenced by the simultaneous test. Keywords: Servant Leadership, Work Motivation, Employee Performance, Organizational Commitment.